Project Oriented Problem Based Learning (POPBL) Model With Ispring Suite Interactive LKPD Assistance to Improve Ability in Poetry Writing - Noviafitri, Kartika Satya; Huda, Mifatkhul (Cetta: Jurnal Ilmu Pendidikan, 2025)
Students' ability to write poetry while learning Indonesian has not been optimally achieved yet. This problem occurs because of the learning models that is not student-cantered. Also, It was often found that learning had not been implemented using the role of media in supporting the student learning process needs to be optimized. In addition, worksheets with comprehensive assessment of poetry writing skills have not been used by teachers. The POPBL (project-oriented learning) model, which combines the role of technology in the form of digital LKPD based on iSpring Suite, is an alternative solution for improving students' writing poetry skills. The use of this worksheet is oriented towards assessing the process according to the indicators of students' poetry writing abilities. This quasi experimental research was carried out using a quantitative approach. The research took place at Muhammadiyah 3 Senior High School Surakarta. There were 30 students as participants from XI IPA 1 and XI IPA 2. The instrument of data collection was utilized to test students' ability in poetry writing. Data analysis was carried out using inferential statistical tests namely independent t-test. The results of the analysis obtained in experimental class 1 showed an increase in the ability to write poetry of 77.47 and in experimental class 2 of 62.87. The independent T test conducted showed that the two groups had significant differences with a significance value of 0.001. The test results showed how class that implement POPBL model and Ispring Suites LKPD media were more optimal rather than the other class in terms of improving students' poetry writing abilities.